Moisture content Determination of Kokilaksha churna (Asteracantha longifolia Nees) . Using Loss on Drying Method: A quality control Approach - Dr. Acharya Maitri Bhaveshkumar; Dr. Satej T. Banne (The Bioscan, 2026)
Background: Kokilaksha (Asteracantha longifolia Nees) is an important Ayurvedic medicinal plant used for its Mutrala, Shothahara, Rasayana, and Balya properties. Mositure content is a critical quality parameter affecting stability, microbial safety, and therapeutic safety, and therapeutic efficacy of powdered herbal drugs. Objective: To determine the moisture content of Kokilaksha Churna using the Loss on Drying (LOD) method. Methods: The powdered drug was procured, authenticated, and analyzed in the Quality Control Laboratory of Parul Institute of Ayurveda. LOD was performed at 110 degree Celsius until constant weight was achieved. Results: The mean moisture content of Kokilaksha Churna was calculated to be 8.0% confirming proper drying and quality. Conclusion: Kokilaksha churna meets quality standards for moisture content. Routine moisture analysis is recommended to ensure stability, safety, and therapeutic efficacy.